Symmetry-adapted density matrix renormalization group calculations of the primary excited states of poly(para-phenylene vinylene). - Bursill, R; Barford, W (2009)
The Pariser-Parr-Pople model of pi-conjugated electrons is solved by a three-block, symmetry-adapted density matrix renormalization group (DMRG) method for the light emitting polymer, poly(para-phenylene vinylene). The energies of the primary excited states are calculated. There is excellent agreement between theory and experiment when solid state screening is incorporated into the model parameters, enabling us to make an identification of the origin of the key spectroscopic features. Appendices describe important technical aspects of the three-block DMRG approach: Local Hilbert space efficiency and its relation to the matrix product formulation of the DMRG; an efficient computational procedure for constructing symmetry-adapted states for DMRG calculations; and correct superblock state targeting to ensure good convergence of the method.